2000
DOI: 10.1172/jci9956
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration activates an NF-κB–driven, COX2-dependent survival mechanism in renal medullary interstitial cells

Abstract: Renal prostaglandin (PG) synthesis is mediated by cyclooxygenase-1 and -2 (COX1 and COX2). After dehydration, the maintenance of normal renal function becomes particularly dependent upon PG synthesis. The present studies were designed to examine the potential link between medullary COX1 and COX2 expression in hypertonic stress. In response to water deprivation, COX2, but not COX1, mRNA levels increase significantly in the renal medulla, specifically in renal medullary interstitial cells (RMICs). Water deprivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
158
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(183 citation statements)
references
References 58 publications
19
158
1
5
Order By: Relevance
“…It has been reported that dehydration upregulates the expression of tonicity-sensitive genes, such as an ion channel (46), a solute cotransporter (47), a metabolic enzyme (48), and heat shock proteins (26,49) in the kidney in vivo. In vivo dehydration also induces the nuclear distribution of TonEBP/OREBP/NFAT5 in thick ascending limbs and the S3 segment (pars recta) of proximal tubules in the rat kidney (50).…”
Section: Probementioning
confidence: 99%
“…It has been reported that dehydration upregulates the expression of tonicity-sensitive genes, such as an ion channel (46), a solute cotransporter (47), a metabolic enzyme (48), and heat shock proteins (26,49) in the kidney in vivo. In vivo dehydration also induces the nuclear distribution of TonEBP/OREBP/NFAT5 in thick ascending limbs and the S3 segment (pars recta) of proximal tubules in the rat kidney (50).…”
Section: Probementioning
confidence: 99%
“…Because the HIV-LTR contains two NF-B enhancer elements that bind a broad range of homodimeric and heterodimeric NF-B complexes (Kretzschmar et al, 1992;Liu et al, 1992;Doerre et al, 1993), HLL transgenic animals have been used as a model to quantify both constitutive and induced NF-B activity in vivo in several organ systems, including the mammary gland Brantley et al, 2000;Hao et al, 2000). Mice heterozygous for the targeted ib␣ allele and hemizygous for the transgene were intercrossed to generate ib␣ Ϫ/Ϫ , ib␣ ϩ/Ϫ , or ib␣ ϩ/ϩ offspring that also harbored the HLL transgene.…”
Section: Ib␣-deficient Mammary Epithelium Displays Increased Ductal Bmentioning
confidence: 99%
“…Similarly, hypertonicity activates NF-B in renal medullary interstitial cells, and water deprivation increases renal NF-B-driven reporter gene expression in transgenic mice (38). In addition, GATA may play a role in tonicity-regulated AQP2 transcription, because hypertonic stress induces transcription of GATA-2 in placental trophoblast stem cells (39).…”
Section: Discussion Mpkccd Cells Are a Proper Model To Study Tonicitymentioning
confidence: 99%